If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(3x + 1) = -70 Reorder the terms: -7(1 + 3x) = -70 (1 * -7 + 3x * -7) = -70 (-7 + -21x) = -70 Solving -7 + -21x = -70 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -21x = -70 + 7 Combine like terms: -7 + 7 = 0 0 + -21x = -70 + 7 -21x = -70 + 7 Combine like terms: -70 + 7 = -63 -21x = -63 Divide each side by '-21'. x = 3 Simplifying x = 3
| x^2+n= | | 720x-14000-x^2=0 | | 2x+12=-7x-24 | | n-10=13+15 | | 3(4y+6)-5=1 | | 29+x+x=180 | | -1/2x+3=1 | | 5=-1/2x+3 | | 5-3[7-(3y-6)]= | | 9+7a=8a+5 | | 5(-1)-3=-2-x | | x^4-4x^3-12x^2+24x+5=0 | | 6(2n-1)+6=-3n | | C=35n+500 | | 6=1/36 | | C=2(3.16)r | | 5x-(x-2)=2x+6 | | 72+28+x=180 | | 3v^2+10=7v^2-15 | | x^4-6x^2+8x-5=0 | | 3a-1=95 | | L+w=36 | | f(x)=(x^2+25)(x^3+2x^2-15x) | | -2.3m=-12 | | 2/5=35/n | | 10-z=23 | | -(15/4)-(7) | | 1+y=3x | | 2.75+1.25+5.5= | | -3(5-9v)=257v | | f(x)=-10x^2+40 | | 3(0)-3y=2(0)+6 |